Kurangnya Minat Berkunjung Peserta Didik SMK Negeri 9 Padang ke Perpustakaan - Susilawati, Endang; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
This paper aims to identify and describe: (1) the benefits of students after a visit to the library, and (2) comparison of the time required learners with the time available to visit the Library SMK Padang 9. Data were collected through observation and interviews with 9 students SMK Padang. Analyzing data descriptively. By analyzing the data, it was concluded the following. First, the benefits of students after a visit to the library. Second, comparison of the time taken by learners is the location of the library is too far away from the classroom makes the students lazy to visit the library. The time taken by learners SMK Padang 9 with time available to visit the library less effective and efficient Keywords: learners; library